Land based abalone culture in re-circulating systems using a recycled freezer container - Kadowaki, Syusaku; Saw, Mya Linn; Yohei, Yamada; Rahman, Mohammad Mustafizur (2013)
To minimize environmental problems associated with aquaculture, we wanted to develop abalone culture approach in small scale re-circulating aquaculture system housed in an air-conditioned recycled freezer container. Protein skimmer (PS) removes organic matter from the water before it breaks down into nitrogenous waste. The aim of this study was to elucidate the effects of PS, shelter and feeding interval on water quality, bacteria count and feed intake, feces excretion, growth and FCR of hybrid abalone (Haliotis discus hannai x H. sieboldi) in a small scale re-circulating system. A frozen container (4.3x1.9x1.9m) was used to maintain optimum water temperature at 19.2±0.8℃ for abalone growth for 87 days. Each system consisted of two bio-filters (100 and 200L) and two abalone culture tanks (each 200L) containing three plastic baskets (50x34x6cm, with 12mm mesh). The abalone stocking density was 20 individuals (5.3±0.8g). PS increased feed intake and shell growth of abalone. Shelter increased abalone growth and FCR. Feed intake was highest at a pattern of 2 days feeding after 1 day none feeding. Results indicate re-circulating abalone culture systems with PS housed in an air-conditioned recycle frozen container may provide a viable alternative to land based, flow through systems.